Isolated complete popliteus tendon rupture following a trivial occupational injury - Abdullah, Arifaizad; Harun, Mohd Hezery; Jamil, Hariati; Abdul Rahim, Ezamin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Traumatic rupture of the popliteus tendon is a rare type of knee injury. Most reported cases had occurred in athletes or following high impact trauma. We report a case of a 23-year-old male with an isolated complete popliteus tendon rupture that was diagnosed arthroscopically. The patient worked as a general labourer in a sawmill. He fell at his workplace and presented with acute painful fixed flexion of the right knee. Initially he was suspected to have a meniscus tear. Diagnostic arthroscopy of the knee was carried out; and diagnosis of popliteal tendon rupture was established. The patient was subsequently managed conservatively by arthroscopic debridement. He was allowed to mobilize the knee as tolerated after the surgery. He was well with a full knee range of movement and was able to walk normally at six weeks after surgery. This article highlights the possibility of complete popliteus tendon rupture following a minor occupational injury in a previously normal knee.